Staging Aural Fugitivity through Nineteenth-Century Freak Show Archives - Bainbridge, Danielle (Performance Matters, 2022)
This essay analyzes aural fugitivity in archives of nineteenth-century freak show performers Millie Christine McKoy and traces the difficulties in staging these archives for twenty-first-century audiences. Aural fugitivity couples theories of Black fugitivity with sound studies analysis of enslavement and nineteenth-century performance in order to explore the legacies of freak show and sideshow performers who were also enslaved. This essay, taking as an object of analysis the author's own creative work based on these archives, traces the biography of the McKoys alongside their performance strategies that resisted full archival capture through fugitive sound.